In vitro activity of ceftolozane/tazobactam versus antimicrobial non-susceptible Pseudomonas aeruginosa clinical isolates including MDR and XDR isolates obtained from across Canada as part of the CANWARD study, 2008–16. (12th December 2017) - Walkty, Andrew; Adam, Heather; Baxter, Melanie; Lagacé-Wiens, Philippe; Karlowsky, James A; Hoban, Daryl J; Zhanel, George G
Abstract: Objectives: Ceftolozane/tazobactam is a novel β-lactam β-lactamase inhibitor combination with a broad spectrum of activity that includes Pseudomonas aeruginosa . The purpose of this study was to evaluate the in vitro activity of ceftolozane/tazobactam and relevant comparators versus a large collection of antimicrobial non-susceptible P. aeruginosa clinical isolates recovered from patients across Canada (CANWARD, 2008–16). Methods: Susceptibility testing was performed on P. aeruginosa clinical isolates obtained from sentinel hospitals across Canada between January 2008 and December 2016 using broth microdilution, as described by the CLSI. MDR P. aeruginosa were defined as isolates that tested non-susceptible to at least one antimicrobial from ≥3 classes. XDR P. aeruginosa were defined as isolates that tested non-susceptible to at least one antimicrobial from ≥5 classes. Results: In total, 3229 P. aeruginosa isolates were obtained as a part of CANWARD. Ceftolozane/tazobactam was the most active antimicrobial evaluated, with 98.3% of isolates testing susceptible. The percentage of antimicrobial non-susceptible isolates that remained susceptible to ceftolozane/tazobactam ranged from 85.3% (amikacin non-susceptible subset) to 95.0% (ciprofloxacin non-susceptible subset). Four-hundred and sixty-two P. aeruginosa isolates were MDR (14.3% of all isolates tested) and 84 were XDR (2.6% of all isolates tested). Ceftolozane/tazobactam demonstrated excellent in vitro activity versus the MDR and XDR isolates, with 90.5% and 78.6% remaining susceptible, respectively. Conclusions: Ceftolozane/tazobactam demonstrated excellent in vitro activity against antimicrobial non-susceptible P. aeruginosa clinical isolates, including MDR and XDR subsets. It may prove useful in the treatment of infections caused by these organisms.